The Influence of Class Culture in the Online Learning Process on Academic Achievement of IPB University Students - Rahmawati, Siti; Hidayati, Nurul; Triyono, Rudi (Jurnal Pendidikan Ilmu Sosial, 2021)
Indonesia is the country with the worst Covid-19 handling and resilience ranking in the world. The Covid-19 pandemic has caused learning activities that were initially carried out face-to-face, have now turned online-based or referred to as online learning. This study aims to analyze the influence of classroom culture on the academic achievement of students of the Management Department of IPB University. The research was conducted in July 2021 – September 2021 involving as many as 213 respondents, namely active students of the Management Department, Faculty of Economics and Management, IPB University with the proportional random sampling method. The data used are primary and secondary data. Primary data comes from distributing questionnaires online using google form. While secondary data comes from sources relevant to the research topic. The data analysis used in this research is descriptive analysis and Structural Equation Modeling Partial Least Square (SEM PLS). The results of the study indicate that the classroom culture that occurs in Management Department students shows the category towards being open with a fairly good perception of assessment. At the 5% level of significance, Class Culture has a significant and positive effect on academic achievement.